Optimalisasi Komponen Forensik dalam Pendidikan Profesi Hukum di Indonesia - Marta Sumarta; Dinata Firmansyah; Rosidin; Kusyana (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren, 2025)
This study examines the critical role of forensic components in enhancing the quality and effectiveness of professional legal education in Indonesia. The increasing complexity of modern criminal cases, including corruption, sexual violence, and other sophisticated crimes, necessitates the integration of forensic knowledgesuch as forensic medicine, forensic linguistics, and evidence analysisinto legal curricula. Using a qualitative approach with library research and thematic content analysis, the study analyzed recent literature, journals, and official documents to identify essential forensic components, evaluate their impact on professional competence, and formulate strategic recommendations for curriculum development. Findings indicate that integrating forensic components equips law graduates with multidisciplinary competencies, ethical awareness, and collaborative skills, enabling them to interpret scientific evidence, analyze verbal and written testimonies, and work effectively with forensic experts. The study proposes a forensic-legal competency framework emphasizing legal knowledge, forensic analytical skills, and ethical-procedural awareness. Implementing structured theoretical and practical forensic training not only improves individual competence but also strengthens the justice system by promoting evidence-based decisions and minimizing errors. This research extends existing legal education theories, offering a foundation for curriculum innovation and future empirical studies on the synergy between law and forensic science, ultimately preparing Indonesian legal professionals to handle complex criminal cases effectively and ethically.